Tantangan Migrasi, Pengelolaan Remitansi, dan Kekerasan terhadap Buruh Migran Perempuan Asal Lombok di Malaysia dan Arab Saudi - Saipul Hamdi (Prodi Sosiologi Universitas Mataram, 2021)
This article aims to understand the migration challenges faced by female migrant workers (TKW) from Lombok who have worked in Saudi Arabia and Malaysia. The challenges faced by female migrant workers are complex, ranging from recruitment and shelter in the country of origin before leaving, and cultural and language issues in the workplace. This article explores these challenges and tries to relate them to the quality level of educational and human resources factors that prospective migrant workers have. Besides, this article also discusses the historical aspects of Sasak women’s involvement and participation in migration and the factors that drove them to take up the profession as migrant workers. The issue of remittance management and violence faced by migrant workers in the employer's home becomes a crucial issue that requires serious attention from the government. Publicly speaking, female migrant workers continue to experience physical and sexual violence resulting in disability and severe trauma. Therefore, this article aims to investigate the forms of violence that befall the female migrant workers.